Hubungan Tinggi Badan dengan Estimasi Panjang Ulna di Desa Pabelan - Istiqomah, Afifah; Nur Hasanah, Laras Eka; Diniyati, Hilda; Panjaitan, Winda Sauci (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2025)
Background: Human physical development is fundamentally characterized by body stature, which represents the cumulative length of skeletal structures forming the anatomical framework and overall body proportions. Anthropometric measurements of body height through various skeletal segment assessments have become essential tools in anatomical, anthropological, and forensic investigations. Objective : This study aimed to investigate the correlation between actual body stature and predicted height derived from ulnar bone measurements among women of reproductive age residing in Pabelan Village. Methods: A cross-sectional observational study employing descriptive-analytical methodology was conducted in Pabelan Village. The study population comprised 32 women aged 15-49 years without history of skeletal fractures affecting the spine, upper limbs, lower limbs, or cervical vertebrae, and free from genetic conditions impacting bone structure. Total sampling technique was utilized for participant selection. Anthropometric data were collected using microtoise for height measurement (precision 0.1 cm) and measuring tape for ulnar length assessment. Statistical analysis was performed using Pearson correlation test via SPSS version 25.0. Results: Pearson correlation analysis revealed a statistically significant positive relationship (r=0.746, p<0.01) between ulnar length and body height, indicating a strong correlation between these anthropometric variables. Conclusions: This investigation demonstrates that ulnar bone dimension serves as a valid predictor for estimating Body Mass Index (BMI) calculations. Furthermore, the study validates World Health Organization inquiries by confirming that arm span measurements possess superior validity compared to knee height measurements, generating height estimates with greater approximation to actual values Keywords: Height Estimation, Ulnar Bone Dimension, Body Stature, Anthropometry